PRIMARY FAMILY CAREGIVER PSYCHOLOGICAL STRESS OF STROKE SURVIVORS AT RSUD DR. H. SLAMET MARTODIRJDJO PAMEKASAN: Stres Psikologis Primary Family Caregiver Penderita Stroke di RSUD Dr. H. Slamet Martodirdjo Pamekasan - Rizkiyah Apriliyanti, Itsnatur; Martini, Santi; Aziz Rahman, Muhammad; D. Dela Rosa, Ronnel (Jurnal Berkala Epidemiologi, 2024)
Background: Primary Family Caregiver (PFC) has a vital role in providing care for stroke survivors and meeting their needs during a long-term recovery period. However, the PFC of stroke survivors experienced stress from a low level to a very high level. Purpose: Research to analyze the PFC psychological stress of stroke survivors has been conducted in Pamekasan. Methods: This type of research is a quantitative, analytic survey, and cross-sectional approach. The research subjects were 103 PFC ischemic stroke survivors who were outpatients at RSUD Dr. H. Slamet Martodirdjo Pamekasan. The sampling technique in this study was simple random sampling. The Depression Anxiety Stress Scale (DASS) questionnaire has been used to measure PFC stress levels. Results: Spearman-Rho analysis between education and stress level showed a correlation coefficient 0.22 with p = 0.02 (p <0.05). This result means that there is a positive relationship between the two variables. However, age, gender, occupation, income, and kinship relationships did not have a significant relationship with the PFC psychological stress of stroke survivors. Conclusion: There is a positive relationship between education and stress levels. Health workers can form the PFC communities to help increase knowledge, skills, and coping strategies.